Inovasi Kepemimpinan Kepala Sekolah Untuk Meningkatkan Profesionalisme Kinerja Guru Di Mts Zia Salsabila Bandar Setia - Laila Qodri; Abdul Fattah Nasution (Universitas Pakuan, 2026)
PRINCIPAL'S LEADERSHIP INNOVATION TO IMPROVE THE PROFESSIONALISM OF TEACHER PERFORMANCE AT MTs ZIA SALSABILA BANDAR SETIA This study examined the principal's leadership innovation at MTs Zia Salsabila to increase teacher professionalism and performance. This qualitative descriptive study uses grounded theory from a phenomenological perspective. Data was collected from principals, teachers, and students through observation, interviews, and documentation. Data analysis includes reducing, presenting, and deriving findings, as well as triangulating sources, methodologies, and ideas to assess their validity. The study found that clear direction, continual mentoring, encouragement to participate in training, the use of technology in learning, English language familiarisation, and discipline enforcement with rewards can innovate principal leadership. Principal commitment, facility and infrastructural support, and teacher encouragement help. Perspective, facilities, human resource readiness, and environment hinder.